2005
DOI: 10.1016/j.visres.2005.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of nitric oxide in the retina

Abstract: Nitric oxide (NO) is the most widespread signaling molecule found in the retina in that it can be made by every retinal cell type. NO is able to influence a wide variety of synaptic mechanisms ranging from increasing or decreasing neurotransmitter release to the modulation of gap junction conductivity. Although biochemical methods can analyze overall levels of NO, such methods cannot indicate the specific cell types involved. In the last few years, fluorescent imaging methods utilizing diaminofluorescein have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
84
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(92 citation statements)
references
References 56 publications
6
84
2
Order By: Relevance
“…Since we determined cGMP levels in the whole retina, our results might suggest that changes in cGMP occurred in different cell populations, which may have differed in their synthesis and degradation activities. Although several groups have concluded that the NO-cGMP pathway modulates the neural circuitry in the inner retina [40-42], the most pronounced effect of dark adaptation in the rat retina is an enhancement of NADPH-d activity in Müller cells. Moreover, Müller cells were reported to be immunonegative for sGC [22], which may explain our results.…”
Section: Discussionmentioning
confidence: 99%
“…Since we determined cGMP levels in the whole retina, our results might suggest that changes in cGMP occurred in different cell populations, which may have differed in their synthesis and degradation activities. Although several groups have concluded that the NO-cGMP pathway modulates the neural circuitry in the inner retina [40-42], the most pronounced effect of dark adaptation in the rat retina is an enhancement of NADPH-d activity in Müller cells. Moreover, Müller cells were reported to be immunonegative for sGC [22], which may explain our results.…”
Section: Discussionmentioning
confidence: 99%
“…In future studies we will directly localize NO increases in response to mAChR activation using NO imaging (Eldred and Blute, 2005). Given the potential interactions with the both glycinergic and GABAergic transmitter systems and the widespread localization of these receptors in both the inner and outer retina, mAChR-stimulated NO production will certainly have many physiological functions in visual processing.…”
Section: Discussionmentioning
confidence: 99%
“…Since it is a gas it is potentially capable of functioning as an intercellular messenger to affect cellular metabolism, although imaging studies suggest that diffusion of NO from cells is much more limited and controlled than had been previously thought (Eldred and Blute, 2005). NO acts through several different biochemical mechanisms to effect downstream targets, including S-nitrosylation (Ignarro and Gruetter, 1980), ADP ribosylation (Brune and Lapetina, 1989), and interaction with heme groups of many proteins (Craven and DeRubertis, 1978).…”
mentioning
confidence: 99%
“…However, our preliminary experiments showed that the muscarinic receptor antagonist atropine did not alter the effects of bright illumination on sodium currents, ruling out this possibility. Nitric oxide (NO) may also be released by light and/or dopamine application in the retina (Eldred and Blute, 2005;Sekaran et al, 2005) and could have modulated the bipolar cell sodium currents. However, in other parts of the CNS, NO increases voltage-gated sodium currents (Hammarstrom and Gage, 1999), which is opposite to our results.…”
Section: Dopamine and Bright Light Contribute To Network Adaptation Bmentioning
confidence: 99%